Heavenbreaker eaudiobook - Wolf, Sara (Heavenbreaker, 2024)
Bravery isn't what you do. It's what you endure. The duke of the powerful House Hauteclare is the first to die. With my dagger in his back. He didn't see it coming. Didn't anticipate the bastard daughter who was supposed to die with her mother—on his order. He should have left us with the rest of the Station's starving, commoner rubbish. Now there's nothing left. Just icy-white rage and a need to make House Hauteclare pay. Every damn one of them. Even if it means riding Heavenbreaker—one of the few enormous machines left over from the War—and jousting against the fiercest nobles in the system. Each win means another one of my enemies dies. And here, in the cold terror of space, the machine and I move as one, intent on destroying each adversary—even if it's someone I care about. Even if it's someone I'm falling for. Only I'm not alone. Not anymore. Because there's something in the machine with me. Something horrifying. Something . . . more . And it won't be stopped. Contains mature themes.